Evolutionary Model of e-Procurement Adoption: A Case of the Vietnam Construction Industry - Tran, Quangdung; Drew, Steve; Stewart, Rodney Anthony (International Journal of Sustainable Construction Engineering and Technology, 2021)
In order to propose more effective solutions to improve the diffusion of e-procurement technologies in the construction sector, it is very important to get a better understanding on the practical evolutionary process of e-procurement adoption at the enterprise level. This cases-study seeks to investigate the strategic evolution of e-procurement adoption in construction companies. Data collected from in-depth semi-structured interviews was analyzed by within-case and cross-case analyses to understand well the similarities and differences between the company cases regarding the way e-procurement technologies have been adopting and implementing. The present study found out a six-stage evolutionary model of e-procurement implementation specific for the context of Vietnamese construction industry. Further, it also proposed the best practical solutions for the cases studied as well as for the general context toward more collaborative e-procurement environment. Although this study is based on the experience of the construction section in a specific country, it is believed its results may be applicable to other developing countries. Using the evolutionary model developed, construction companies are able to self-assess and locate their e-procurement adoption level, and so that establish appropriate practical solutions to move forward a higher level of e-procurement applicability.